2013
DOI: 10.1590/1516-3180.2013.1313478
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate food intake among adults living with HIV

Abstract: CONTEXT AND OBJECTIVE: The number of people living with HIV (PLHIV) in Brazil is between 600,000 and 890,000. Assessing the diet is important in planning healthcare actions and improving PLHIV's quality of life. This study aimed to estimate the prevalence of inappropriate protein, total fat, saturated fat, carbohydrate, fiber, sodium, calcium and cholesterol intake among PVHIV on highly-active antiretroviral therapy (HAART). DESIGN AND SETTING: Cross-sectional study in nine Specialized STD/AIDS Healthcare Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
6
1
1
Order By: Relevance
“…However, this is lower than that of Thapa et al [23], which revealed that one in five PLWHA was underweight. Also, the prevalence of obesity/overweight found in this study is lower than those found in the studies by Giudici, Duran, and Jaime [24] and Nzeagwu and Uwaegbute [22]. In these studies, the researchers found 34% and 36.7% respectively, were overweight/obese.…”
Section: Discussioncontrasting
confidence: 78%
“…However, this is lower than that of Thapa et al [23], which revealed that one in five PLWHA was underweight. Also, the prevalence of obesity/overweight found in this study is lower than those found in the studies by Giudici, Duran, and Jaime [24] and Nzeagwu and Uwaegbute [22]. In these studies, the researchers found 34% and 36.7% respectively, were overweight/obese.…”
Section: Discussioncontrasting
confidence: 78%
“…Also, a systematic review by Schuelter-Trevisol et al (2012) revealed that up to 73% of PLHIV were sedentary [31]. Finally, research has shown that PLHIV were more likely to exceed intake recommendations for saturated fat [32, 33] and dietary cholesterol [34]. …”
Section: Resultsmentioning
confidence: 99%
“…With regard to micronutrients, a study conducted in Brazil has shown low calcium intake [28] in patients with HIV on HAART, whereas other studies have reported low intake of vitamins A, C, E, and B 6 [31]. The low intake of vitamins and minerals, compounded by a poor nutritional status, resulting from either malnutrition or overweight, can adversely affect the immune system [17].…”
Section: Dietary Intake Of Patients With Hiv On Haart With Dyslipidemiamentioning
confidence: 99%